2016
DOI: 10.1523/eneuro.0019-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Subthalamic Deep Brain Stimulation on Intertemporal Decision-Making in Parkinson Patients

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is a widely used treatment for the motor symptoms of Parkinson’s disease (PD). DBS or pharmacological treatment is believed to modulate the tendency to, or reverse, impulse control disorders. Several brain areas involved in impulsivity and reward valuation, such as the prefrontal cortex and striatum, are linked to the STN, and activity in these areas might be affected by STN-DBS. To investigate the effect of STN-DBS on one type of impulsive decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 78 publications
1
8
1
Order By: Relevance
“…Impulsivity scores on the Barratt Impulsiveness Scale (BIS-11, Patton and Stanford, 1995) were measured in six studies (total of 165 patients) comparing scores either between DBS On and Off conditions (Torta et al, 2012;Seinstra et al, 2016), or between DBS On and PD-patients On medication or healthy controls (Hälbig et al, 2009;Evens et al, 2015;Hagelweide et al, 2018;Irmen et al, 2019). One study reported significantly worse impulsivity scores in a DBS-group compared to healthy controls (Hälbig et al, 2009).…”
Section: Clinical Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Impulsivity scores on the Barratt Impulsiveness Scale (BIS-11, Patton and Stanford, 1995) were measured in six studies (total of 165 patients) comparing scores either between DBS On and Off conditions (Torta et al, 2012;Seinstra et al, 2016), or between DBS On and PD-patients On medication or healthy controls (Hälbig et al, 2009;Evens et al, 2015;Hagelweide et al, 2018;Irmen et al, 2019). One study reported significantly worse impulsivity scores in a DBS-group compared to healthy controls (Hälbig et al, 2009).…”
Section: Clinical Scalesmentioning
confidence: 99%
“…Four studies measured DBS-related delay discounting in a total of 108 PD patients ( Table 2; Torta et al, 2012;Evens et al, 2015;Seinstra et al, 2016;Seymour et al, 2016). None of these studies found evidence that DBS activation interferes with subjects' ability to delay claiming a reward in order to maximize total reward, suggesting that DBS does not affect this aspect of impulsivity.…”
Section: Delay Discountingmentioning
confidence: 99%
“…In addition, researchers can leverage implanted DBS electrodes as a neuromodulation tool to study the role of the STN in an extra-operative setting. As such, numerous researchers have utilized this approach to interrogate the function of the STN in conflict ( Frank et al, 2007 ; Schroeder et al, 2002 ), decision-making ( Seymour et al, 2016 ; Seinstra et al, 2016 ; Wylie et al, 2010 ; Zaehle et al, 2017 ; Cavanagh et al, 2011 ), and emotional processing ( Le Jeune et al, 2008 ; Le Jeune et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…This could potentially be problematic and result in test-retest effects confounding the results. In addition, not all studies included HCs [33][34][35][36] and thirteen studies [23,[27][28][29]33,35,[37][38][39][40][41][42][43] did not test patients off medication, which contributes to the uncertainty about effects of medication. Thus, it remains unclear to what extent decision-making is impaired in PD and to what degree dopaminergic medication impacts decisionmaking processes.…”
Section: Methodsmentioning
confidence: 99%
“…jumping to conclusions) in patients on medication compared to patients off medication [32,52] as well as in patients receiving polytherapy (L-dopa and DA) relative to L-dopa monotherapy [37,38,43]. Seinstra et al [36] found no effects of DBS or dopaminergic medication when measuring delay-discounting behavior, used to evaluate impulsive choice. However, since all patients in the study had STN-DBS implanted this could potentially be different in comparison to patients only on medication.…”
Section: Uncategorized Tasksmentioning
confidence: 99%